Cloning and expression analysis of Drosophila extracellular Cu Zn superoxide dismutase. Issue 6 (23rd December 2014) - Blackney, Michael J.; Cox, Rebecca; Shepherd, David; Parker, Joel D.
Abstract : Extracellular superoxide dismutase (SOD3) in Drosophila is characterized for mRNA splice variants and sex-specific expression. A SOD3 mutant reveals no effect on longevity, enhanced resistance to paraquat and H2 02, and provided evidence suggesting an interaction with other superoxide dismutases. Abstract : In the present study, we cloned and sequenced the mRNAs of the Sod3 [extracellular Cu Zn SOD (superoxide dismutase)] gene in Drosophila and identified two mRNA products formed by alternative splicing. These products code for a long and short protein derived from the four transcripts found in global expression studies (Flybase numbers Dmel\CG9027, FBgn0033631). Both mRNA process variants contain an extracellular signalling sequence, a region of high homology to the Sod1 (cytoplasmic Cu Zn SOD) including a conserved AUG start, with the longer form also containing a hydrophobic tail. The two fully processed transcripts are homologous to Caenorhabditis elegans Sod3 mRNA showing the same processing pattern. Using an established KG p-element+ insertion line (KG06029), we demonstrate that the Sod3 codes for an active Cu Zn SOD. We found differing expression patterns across sex with higher levels of expression of Sod3 in females. There is a correlation of Sod1 and Sod3 gene expression and activity that can explain why Sod3 was not seen in earlier studies of Sod1 . Finally, we found no effect on lifespan with the Sod3 hypomorph mutation ( Sod3 KG06029 ) but did observe a significant increase in resistance to paraquat and H2 O2 (hydrogen peroxide).